2014
DOI: 10.4103/2230-8210.129115
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of cutaneous manifestations in diabetes mellitus in a tertiary care Hospital of Eastern India

Abstract: Background:Diabetes mellitus and its impact on the human body have been extensively dissected over the years. However, skin which is the largest organ in the body, has received minimum attention. Therefore, this study was designed to analyze the prevalence and pattern of skin disorders among diabetic patients from Eastern region of India.Materials and Methods:This is an observational study, conducted in the General Medicine and Endocrinology departments of a Medical College and Hospital in Eastern India. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
45
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 9 publications
13
45
2
1
Order By: Relevance
“…16 Chatterjee et al showed that among 680 diabetic patients 12 patients were newly diagnosed. 17 In our study, majority 50.58% were <5 years, 27.05% in 6 to 10 years, 11.76% in 16 to 20 years and 10.85% in 11 to 15 years. Study by Kumar et al showed that the duration of diabetes was <10 years in 30 patients, 17 had 11-20 years and 3 had > 20 years of diabetes.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…16 Chatterjee et al showed that among 680 diabetic patients 12 patients were newly diagnosed. 17 In our study, majority 50.58% were <5 years, 27.05% in 6 to 10 years, 11.76% in 16 to 20 years and 10.85% in 11 to 15 years. Study by Kumar et al showed that the duration of diabetes was <10 years in 30 patients, 17 had 11-20 years and 3 had > 20 years of diabetes.…”
Section: Discussionsupporting
confidence: 43%
“…16 Chatterjee et al showed that four forty one (64.8%) were male and two thirty nine (35.1%) were female. 17 But no similar results were found in study by Timshina et al, the majority was females (54.95%) who were diabetic as compared to males (45.1%). 19 In our study, majority 57.5% were new cases and 42.5% were known cases.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Mandal et al & chatterjee et al [5,6] found that in dengue epidemic in the year 2012 most common manifestations were retro orbital pain, myalgia and amongst gastro intestinal manifestation abdominal pain, diarrhea and vomiting were present. In our study, total 103 dengue MAC ELISA positive or Dengue NS1Ag ELISA positive or both patients were included and analyzed.…”
Section: Discussionmentioning
confidence: 99%